2019
DOI: 10.18535/ijmsci/v6i9.03
|View full text |Cite
|
Sign up to set email alerts
|

Study of Relation between Serum Magnesium Levels and Vascular Complications in Patients of Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus is increasing alarmingly especially in developing country like India. The complications related to Diabetes lead to loss of life and also healthy life years lost. There are many factors contributing to the compications. The prevalance of magnisiuria in diabetics is long under reasearch. Magnesium is known to be important for endothelial function. We studied the prevalance of levels of magnesium in patients who had vascular complications associated with diabetes. We found a correlation that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…34 Dineshbabu and Tonk in their recent study concluded hypomagnesemia in T2DM was correlated with various complications and stated magnesium can be considered as a nutritional supplement in patients with diabetes to reduce the incidence of vascular complications. 35 Subjects with type 2 diabetes showed a strong relationship with foot ulcers with depleted serum magnesium. 36 Duration of diabetic foot ulcers (grade I and II) increased with duration of diabetes increase and serum magnesium decrease.…”
Section: Discussionmentioning
confidence: 99%
“…34 Dineshbabu and Tonk in their recent study concluded hypomagnesemia in T2DM was correlated with various complications and stated magnesium can be considered as a nutritional supplement in patients with diabetes to reduce the incidence of vascular complications. 35 Subjects with type 2 diabetes showed a strong relationship with foot ulcers with depleted serum magnesium. 36 Duration of diabetic foot ulcers (grade I and II) increased with duration of diabetes increase and serum magnesium decrease.…”
Section: Discussionmentioning
confidence: 99%